Binder for secondary battery electrode and use thereof
By using crosslinked polymers and multifunctional compounds containing cationic groups in the secondary battery electrode, the problem of insufficient strength and toughness of the adhesive coating is solved, and the circulation characteristics and electrolyte resistance of the secondary battery are significantly improved. , achieving better electrode durability.
Patent Information
- Application Number
- CN202380035833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-27
- Filing Date
- 2023-04-03
- Publication Date
- 2024-12-17
AI Technical Summary
The existing adhesive for secondary battery electrodes has insufficient strength and toughness after the electrolyte is impregnated, resulting in insufficient electrolyte resistance of the secondary battery electrode mixed material layer, which affects the circulation characteristics.
A binder containing a crosslinked polymer or a salt thereof is used. The crosslinked polymer contains an ethylenically unsaturated carboxylic acid monomer structural unit, and the carboxyl group is combined with a cationic group, and a multifunctional cationic group-containing compound is used to Improve the crosslinking degree of the adhesive and the electrolyte resistance of the electrode mixture layer.
The strength and toughness of the adhesive coating film after the electrolyte impregnation and the circulation characteristics of the secondary battery electrode are significantly improved, and the durability of the electrode is enhanced.
Smart Images

Figure BDA0005097858310000271 
Figure BDA0005097858310000321
Abstract
Description
Technical Field
[0001] The present invention relates to a binder for secondary battery electrodes and use thereof. Background Art
[0002] As secondary batteries, various power storage devices such as nickel-metal hydride secondary batteries, lithium-ion secondary batteries, and double-layer capacitors are put into practical use. These electrodes for secondary batteries are made by coating and drying the composition on the collector, wherein the composition is a composition for forming an electrode mixture layer containing an active material and an adhesive. For example, in lithium-ion secondary batteries, as an adhesive for a negative electrode mixture layer composition, an aqueous adhesive containing styrene butadiene rubber (SBR) latex and carboxymethyl cellulose (CMC) is used. On the other hand, as an adhesive for a positive electrode mixture layer, N-methyl-2-pyrrolidone (NMP) solution of polyvinylidene fluoride (PVDF) is widely used.
[0003] In recent years, with the expansion of the use of various secondary batteries, the demand for improving energy density, reliability and durability has tended to increase. For example, in order to increase the capacitance of lithium-ion secondary batteries, the use of silicon-based active materials as negative electrode active materials has increased. However, it is known that silicon-based active materials have a large volume change during charge and discharge, and the electrode mixture layer may peel off or fall off with repeated use, resulting in a problem of reduced battery capacity and deterioration of cycle characteristics (durability). In order to suppress such defects, studies have been conducted to improve durability by firmly bonding active materials with a binder (adhesiveness), reducing the size of active materials to alleviate stress associated with swelling and shrinkage, or studying additives to the electrolyte.
[0004] Among them, it is reported that acrylic polymers are effective as a binder having good cycle characteristics and achieving an effect of improving the durability of a negative electrode mixture layer using a silicon-based active material. Patent Document 1 discloses a binder containing a cross-linked acrylic acid polymer cross-linked with polyacrylic acid by a specific cross-linking agent, and discloses that the electrode structure is not destroyed even when an active material containing silicon is used, and good cycle characteristics are shown. Although the binder disclosed in Patent Document 1 can provide good cycle characteristics, there is a tendency to increase the ratio of silicon-based active materials in order to improve the performance of secondary batteries, and a binder that can obtain higher cycle characteristics is needed.
[0005] As a binder for secondary battery electrodes that can improve the cycle characteristics of secondary batteries, for example, Patent Document 2 discloses a binder for secondary battery electrodes, wherein the binder for secondary battery electrodes contains a binder and a cross-linking agent, wherein the binder contains a copolymer of vinyl alcohol and an alkali metal neutralizer of an olefinically unsaturated carboxylic acid, and the cross-linking agent has two or more functional groups that can react with carboxyl groups and / or hydroxyl groups in the binder. In addition, Patent Document 3 discloses a binder for secondary battery electrodes, which contains a polymer and 0.1 parts by mass or more and 8 parts by mass or less of an organic compound (cross-linking agent), wherein the polymer has a functional group capable of binding to a cationic group, and the organic compound has two or more cationic groups and a weight-average molecular weight of 300 or more and less than 10,000. Prior art literature Patent Literature
[0006] Patent Document 1: International Publication No. 2014 / 065407 Patent Document 2: International Publication No. 2019 / 054348 Patent Document 3: International Publication No. 2017 / 150048 Summary of the invention Technical problem to be solved by the invention
[0007] The binders for secondary battery electrodes disclosed in Patent Documents 2 and 3 both contain non-cross-linked polymers, which have problems due to the following situations: although good cycle characteristics are obtained through the reaction between the functional groups in the polymer and the functional groups in the cross-linking agent, they are insufficient; and due to the insufficient toughness of the binder coating after immersion in the electrolyte, the electrolyte resistance of the secondary battery electrode mixed material layer is insufficient.
[0008] The present invention is an invention completed in view of such a situation, and its purpose is to provide a secondary battery electrode adhesive that can improve the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery. In addition, a secondary battery electrode mixture layer composition containing the above-mentioned adhesive, a secondary battery electrode obtained using the composition, and a secondary battery are also provided.
[0009] The present inventors conducted intensive research to solve the above-mentioned problems and found that by using an adhesive for secondary battery electrodes containing a cross-linked polymer or a salt thereof, the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery are improved, thereby completing the present invention, wherein the cross-linked polymer or a salt thereof contains a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, and at least a portion of the carboxyl group is a functional group for bonding to a cationic group.
[0010] The present invention is as follows. [1] A binder for secondary battery electrodes, the binder for secondary battery electrodes comprising a cross-linked polymer containing a carboxyl group or a salt thereof, wherein at least a part of the carboxyl group is a functional group for bonding to an organic compound, and the organic compound is an organic compound having two or more cationic groups. [2] The binder for secondary battery electrodes according to [1], further comprising an organic compound having two or more cationic groups, wherein the cationic groups are reactive with carboxyl groups (hereinafter also referred to as "polyfunctional cationic group-containing compound"). [3] The binder for secondary battery electrodes according to [2], wherein the polyfunctional cationic group-containing compound is contained so that the molar ratio of the cationic group to the carboxyl group of the cross-linked polymer is 0.05 or more and 3.0 or less. [4] The binder for secondary battery electrodes according to [2] or [3], wherein the molecular weight of the polyfunctional cationic group-containing compound is 300 or more and 100,000 or less. [5] The binder for secondary battery electrodes according to any one of [2] to [4], wherein the polyfunctional cationic group-containing compound contains at least one selected from the group consisting of polyethyleneimine, polyethyleneimine derivatives and polyetheramines. [6] The binder for secondary battery electrodes according to any one of [1] to [5], wherein the carboxyl group-containing cross-linked polymer contains 50% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer relative to all structural units thereof. [7] The binder for secondary battery electrodes as described in any one of [1] to [6], wherein the cross-linked polymer is a cross-linked polymer obtained by polymerizing a monomer composition containing a non-cross-linking monomer and a cross-linking monomer (but different from the polyfunctional cationic group-containing compound). [8] The binder for secondary battery electrodes according to [7], wherein the amount of the crosslinkable monomer used is 0.001 mol % or more and 2.5 mol % or less relative to the total amount of the non-crosslinkable monomer. [9] The binder for secondary battery electrodes according to any one of [1] to [8], wherein the crosslinked polymer has a particle size measured in an aqueous medium after being neutralized to a degree of neutralization of 80 mol % to 100 mol % and a volume-based median diameter of 0.1 μm or more and 10.0 μm or less.
[10] A composition for a secondary battery electrode mixture layer, comprising the binder for a secondary battery electrode according to any one of [1] to [9], an active material, and water.
[11] The composition for a secondary battery electrode mixture layer according to
[10] , wherein the active material contains a silicon-based active material.
[12] A secondary battery electrode comprising a mixture layer formed from the composition for a secondary battery electrode mixture layer according to
[10] or
[11] on a surface of a current collector.
[13] A secondary battery comprising the secondary battery electrode according to
[12] . Beneficial Effects
[0011] According to the binder for secondary battery electrodes of the present invention, the toughness of the binder coating after being impregnated with an electrolyte, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery can be improved. DETAILED DESCRIPTION
[0012] The adhesive for secondary battery electrodes of the present invention (hereinafter also referred to as "the present adhesive") contains a cross-linked polymer containing a carboxyl group (hereinafter also referred to as "the present cross-linked polymer") or a salt thereof (hereinafter also referred to as "the present cross-linked polymer salt"), and can be prepared into a composition for a secondary battery electrode mixture layer (hereinafter also referred to as "the present composition") by mixing an organic compound having two or more cationic groups and the cationic group having reactivity with the carboxyl group (a multifunctional compound containing a cationic group), an active substance, and water. From the viewpoint of achieving the effect of the present invention, the above-mentioned composition is preferably an electrode slurry in a slurry state that can be applied to a collector, and can also be modulated into a wet powder state so that it can cope with stamping processing on the surface of the collector. The secondary battery electrode of the present invention can be obtained by forming a mixture layer formed by the above-mentioned composition on the surface of a collector such as copper foil or aluminum foil. Here, the present binder is preferably used in a composition for a secondary battery electrode mixture layer, and when the composition contains a silicon-based active material as an active material, as described below, from the viewpoint that the effects achieved by the present invention are particularly remarkable.
[0013] Hereinafter, the polyfunctional cationic group-containing compound, the present crosslinked polymer and the method for producing the same, the secondary battery electrode mixture layer composition obtained by using the present binder, the secondary battery electrode, and the secondary battery are described in detail. In the present specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl" means acryloyl and / or methacryloyl. In the numerical ranges recorded in stages in this specification, the upper limit value or lower limit value recorded in one numerical range may be replaced by the upper limit value or lower limit value of the numerical range recorded in other stages, and the upper limit value or lower limit value of the numerical range may also be replaced by the value shown in the embodiment.
[0014] 1. Multifunctional compounds containing cationic groups The polyfunctional cationic group-containing compound is an organic compound having two or more cationic groups, wherein the cationic group is a functional group reactive with the "carboxyl group contained in the present adhesive." In the present invention, the cationic group means a functional group that exists as a cation in water. The polyfunctional cationic group-containing compound is not particularly limited as long as it is an organic compound having a plurality of cationic groups reactive with “the carboxyl groups contained in the present binder” in one molecule. Examples of the cationic group include a substituted or unsubstituted amino group (—NH 2 、-NHR 1 、-NR 1 R 2 、-N + R 1 R 2 R 3 Here, R 1 ~R 3 represents an arbitrary substituent. ), an imino group (=NH), an oxazoline group and other nitrogen-containing functional groups (excluding an amide group), and the like. Among them, from the viewpoint of making the polyfunctional cationic group-containing compound interact well with the present crosslinked polymer, ensuring the viscosity stability of the electrode mixture material layer composition, and further improving the electrolyte resistance of the electrode mixture material layer and the cycle characteristics of the secondary battery, primary amino groups (unsubstituted amino groups, -NH 2 ), secondary amino group (-NHR 1 ), imino group, and more preferably a primary amino group. In addition, the polyfunctional cationic group-containing compound may have only one type of cationic group, or may have two or more types of cationic groups. In addition, the polyfunctional cationic group-containing compound may be a non-polymer or a polymer.
[0015] The polyfunctional cationic group-containing compound is an organic compound having two or more substituted or unsubstituted amino groups (hereinafter also referred to as an "amino group-containing compound"), and is classified into two types: non-polymeric amino group-containing compounds and polymeric amino group-containing compounds. Examples of the non-polymeric amino group-containing compound include ethylenediamine, 1,4-diaminobutane, triethylenetetramine, phenylenediamine, 4,4'-diaminodiphenyl ether, N,N'-bis(3-phenyl-2-propenylene)-1,6-hexanediamine, and dianilines. Examples of the amino group-containing polymer include: Polyethyleneimine; Poly (N-hydroxyethyleneimine), carboxymethylated polyethyleneimine sodium salt and other polyethyleneimine derivatives; Polypropylene imine; Poly (N-2-dihydroxypropyleneimine) and other polypropyleneimine derivatives; Polyallylamine; Poly(allylamine) derivatives such as poly(dimethyldiallylammonium) halides; Polyetheramines such as polyoxypropylene diamine, triethylene glycol diamine, methoxy poly(oxyethylene / oxypropylene)-2-propylamine, trimethylolpropane poly(oxypropylene) triamine, and glycerol poly(oxypropylene) triamine; An aminoethylated acrylic polymer obtained by aminoethylating an acrylic polymer; Cationized cellulose obtained by modifying a cellulose derivative (hydroxyethyl cellulose, carboxymethyl cellulose, etc.) with a cationizing agent having a substituted or unsubstituted amino group. Among them, from the viewpoint of being able to further improve the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer and the cycle characteristics of the secondary battery, polyethyleneimine, polyethyleneimine derivatives and polyetheramines are preferred, polyethyleneimine and polyetheramines are more preferred, and polyethyleneimine is further preferred.
[0016] Here, from the viewpoint of being able to further improve the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer and the cycle characteristics of the secondary battery, the molecular weight of the polyfunctional cationic group-containing compound is preferably 300 to 100,000, more preferably 400 to 70,000, further preferably 600 to 50,000, further preferably 2,000 to 30,000, further preferably 5,000 to 20,000, and further preferably 7,000 to 15,000. In the present invention, when the polyfunctional cationic group-containing compound is polyethyleneimine or a polyethyleneimine derivative, the molecular weight means the number average molecular weight, and for accurate measurement, when the number average molecular weight is 10,000 or less, it can be measured by a boiling point rise method, and when it is greater than 10,000, it can be measured by a viscosity method. In addition, when the polyfunctional cationic group-containing compound is a polyetheramine, the molecular weight means the weight average molecular weight, and it can be measured by gel permeation chromatography (eluent: tetrahydrofuran, standard substance: polyethylene glycol, hereinafter referred to as "GPC method").
[0017] 2. The cross-linked polymer The crosslinked polymer may have a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a)"). A monomer component including the component (a) may be introduced into the polymer by precipitation polymerization or dispersion polymerization.
[0018] <Structural Unit Derived from Ethylenically Unsaturated Carboxylic Acid Monomer> The present cross-linked polymer may have a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "(a) component".). When the present cross-linked polymer has a carboxyl group by having such a structural unit, the desolvation effect of lithium ions and the ion conductivity are excellent while the adhesion to the collector is improved, so that an electrode with low resistance and excellent high-rate characteristics can be obtained. In addition, since water-swellability is imparted, the dispersion stability of the active material in the present composition can be improved. The component (a) can be introduced into the polymer by, for example, polymerizing a monomer containing an ethylenically unsaturated carboxylic acid monomer. Alternatively, it can be obtained by (co)polymerizing a (meth)acrylate monomer and then hydrolyzing it. Alternatively, it can be obtained by polymerizing (meth)acrylamide and (meth)acrylonitrile and then treating them with a strong base, or by reacting an acid anhydride with a polymer having a hydroxyl group.
[0019] As ethylenically unsaturated carboxylic acid monomers, for example, (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid; (meth)acrylamide alkyl carboxylic acids such as (meth)acrylamide caproic acid and (meth)acrylamide dodecanoic acid; succinic acid monohydroxyethyl (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, β-carboxyethyl (meth)acrylate and other carboxyl-containing ethylenically unsaturated monomers or their (partial) alkaline neutralizations, one of which may be used alone or two or more may be used in combination. Among the above, compounds having an acryloyl group as a polymerizable functional group are preferred, and acrylic acid is particularly preferred, from the viewpoint that the polymerization rate is fast and a polymer with a long primary chain length (primary chain length) is obtained, and the bonding strength of the adhesive becomes good. When acrylic acid is used as an ethylenically unsaturated carboxylic acid monomer, a polymer with a high carboxyl content can be obtained.
[0020] The content of component (a) in the present cross-linked polymer is preferably 50% by mass or more and 100% by mass or less relative to all structural units of the present cross-linked polymer. By containing component (a) in the above range, the electrolyte resistance of the secondary battery electrode mixture layer and the cycle characteristics of the secondary battery can be further improved. In the case where the lower limit is 60% by mass or more, it is preferred because the electrolyte resistance of the secondary battery electrode mixture layer and the cycle characteristics of the secondary battery can be further improved; for example, it can be 70% by mass or more, and for example, it can be 80% by mass or more, and for example, it can be 87.5% by mass or more. In addition, the upper limit is, for example, 99% by mass or less, and for example, 98% by mass or less, and for example, 95% by mass or less, and for example, 90% by mass or less, and for example, 85% by mass or less, and for example, 80% by mass or less.
[0021] <Other structural units> In addition to the component (a), the cross-linked polymer may contain other structural units derived from ethylenically unsaturated monomers that can be copolymerized with them (hereinafter also referred to as "component (b)"). As the component (b), for example, structural units derived from ethylenically unsaturated monomers containing hydroxyl groups (monomers represented by the following formula (1) and monomers represented by the following formula (2)), ethylenically unsaturated monomer compounds having anionic groups other than carboxyl groups such as sulfonic acid groups and phosphoric acid groups, or nonionic ethylenically unsaturated monomers can be cited. These structural units can be introduced by copolymerizing monomers including ethylenically unsaturated monomers containing hydroxyl groups, ethylenically unsaturated monomer compounds having anionic groups other than carboxyl groups such as sulfonic acid groups and phosphoric acid groups, or nonionic ethylenically unsaturated monomers. CH 2 =C(R 1 )COOR 2 (1) [Where R 1represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group having 1 to 8 carbon atoms and having a hydroxyl group, (R 3 O) m H or R 4 O[CO(CH 2 ) 5 O] n H. In addition, R 3 represents an alkylene group having 2 to 4 carbon atoms, R 4 represents an alkylene group having 1 to 8 carbon atoms, m represents an integer of 2 to 15, and n represents an integer of 1 to 15.] CH 2 =C(R 5 )CONR 6 R 7 (2) [Where R 5 represents a hydrogen atom or a methyl group, R 6 represents a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms, R 7 represents a hydrogen atom or a monovalent organic group.]
[0022] The proportion of the component (b) may be 0% by mass or more and 50% by mass or less relative to the total structural units of the present cross-linked polymer. The proportion of the component (b) may be 1% by mass or more and 50% by mass or less, 2% by mass or more and 50% by mass or less, 5% by mass or more and 50% by mass or less, or 10% by mass or more and 50% by mass or less. In addition, when the component (b) is contained in an amount of 1% by mass or more relative to the total structural units of the present cross-linked polymer, the affinity for the electrolyte is improved, so that the lithium ion conductivity can be expected to be improved.
[0023] From the viewpoint that the adhesive containing the present crosslinked polymer salt has excellent adhesiveness, the component (b) is preferably a hydroxyl group-containing ethylenically unsaturated monomer among those mentioned above. Furthermore, from the viewpoint of obtaining an electrode having good bending resistance, a structural unit derived from a nonionic ethylenically unsaturated monomer is preferred. Examples of the nonionic ethylenically unsaturated monomer include (meth)acrylamide and its derivatives, nitrile group-containing ethylenically unsaturated monomers, and alicyclic structure-containing ethylenically unsaturated monomers.
[0024] The monomer represented by the above formula (1) is a (meth)acrylate compound having a hydroxyl group. 2In the case of a monovalent organic group having 1 to 8 carbon atoms and having a hydroxyl group, the number of the hydroxyl group may be only one or may be two or more. The monovalent organic group is not particularly limited, and examples thereof include alkyl groups that may have a linear, branched, or cyclic structure, aryl groups, and alkoxyalkyl groups. 2 for (R 3 O) m H or R 4 O[CO(CH 2 ) 5 O] n In the case of H, R 3 or R 4 The alkylene group represented may be a linear or branched chain.
[0025] Examples of the monomer represented by the formula (1) include hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, and hydroxyoctyl (meth)acrylate; polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polybutylene glycol mono(meth)acrylate, and polyethylene glycol mono(meth)acrylate. Polyalkylene glycol mono(meth)acrylates such as polypropylene glycol mono(meth)acrylate; dihydroxyalkyl(meth)acrylates such as glycerol mono(meth)acrylate; caprolactone-modified hydroxymethacrylate (manufactured by Daicel Corporation, trade names "Placcell FM1", "Placcell FM5", etc.), caprolactone-modified hydroxyacrylate (manufactured by Daicel Corporation, trade names "Placcell FA1", "Placcell FA10L", etc.), etc. Regarding the monomer represented by the above formula (1), one of them may be used alone, or two or more of them may be used in combination.
[0026] The monomer represented by the above formula (2) is a (meth)acrylamide derivative having a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms. 7 represents a hydrogen atom or a monovalent organic group. The monovalent organic group is not particularly limited, and examples thereof include alkyl groups that may have a linear, branched, or cyclic structure, aryl groups, and alkoxyalkyl groups, preferably organic groups having 1 to 8 carbon atoms. 7 It may be a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms.
[0027] Examples of the monomer represented by the formula (2) include hydroxy(meth)acrylamide; (meth)acrylamide derivatives having a hydroxyalkyl group having 1 to 8 carbon atoms, such as N-hydroxyethyl(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-hydroxybutyl(meth)acrylamide, N-hydroxyhexyl(meth)acrylamide, N-hydroxyoctyl(meth)acrylamide, N-methylhydroxyethyl(meth)acrylamide, and N-ethylhydroxyethyl(meth)acrylamide; and N,N-dihydroxyalkyl(meth)acrylamide, such as N,N-dihydroxyethyl(meth)acrylamide and N,N-dihydroxyethyl(meth)acrylamide. The monomer represented by the formula (2) may be used alone or in combination of two or more.
[0028] Examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide compounds such as N-isopropyl (meth)acrylamide and N-tert-butyl (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide compounds such as N-n-butoxymethyl (meth)acrylamide and N-isobutoxymethyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamide compounds such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide. Any one of these may be used alone or in combination of two or more.
[0029] As the ethylenically unsaturated monomer containing a nitrile group, for example, there can be mentioned: (meth) acrylonitrile; (meth) cyanoalkyl acrylate compounds such as (meth) cyanomethyl acrylate and (meth) cyanoethyl acrylate; cyano group-containing unsaturated aromatic compounds such as 4-cyanostyrene and 4-cyano-α-methylstyrene; 1,1-biscyanoethylene (シアンビニリデン); one of them can be used alone, or two or more can be used in combination. From the viewpoint of a large content of nitrile groups, acrylonitrile is preferred among the above.
[0030] Examples of the ethylenically unsaturated monomer containing an alicyclic structure include cycloalkyl (meth)acrylates which may have an aliphatic substituent such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, and cyclododecyl (meth)acrylate; isobornyl (meth)acrylate, adamantyl (meth)acrylate, cyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dipentylcyclo (meth)acrylate; and cycloalkyl polyol mono(meth)acrylates such as cyclohexanedimethanol mono(meth)acrylate and cyclodecane dimethanol mono(meth)acrylate. Any of these may be used alone or in combination of two or more.
[0031] From the viewpoint of excellent adhesiveness of the adhesive, the cross-linked polymer preferably contains structural units derived from the monomer represented by the above formula (1), the monomer represented by the above formula (2), (meth)acrylamide and its derivatives, ethylenically unsaturated monomers containing nitrile groups, ethylenically unsaturated monomers containing alicyclic structures, etc. Among them, from the viewpoint of excellent adhesiveness improvement effect of the present adhesive, structural units derived from the monomer represented by the above formula (1) and the monomer represented by the above formula (2) are more preferred as component (b). Among the monomers represented by the above formula (1), hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 8 carbon atoms are more preferred, and 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are still more preferred. In addition, among the monomers represented by the above formula (2), (meth)acrylamide derivatives having a hydroxyalkyl group having 1 to 8 carbon atoms are still more preferred, and N-hydroxyethyl (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, and N-hydroxybutyl (meth)acrylamide are still more preferred.
[0032] In addition, as (b) component, when importing the structural unit of the hydrophobic ethylenically unsaturated monomer with solubility in water being less than 1g / 100ml, it is possible to achieve strong interaction with the electrode material, and good cohesiveness can be exerted to the active material. Thus, a firm and good integrated electrode mixture layer can be obtained, therefore, as the above-mentioned "hydrophobic ethylenically unsaturated monomer with solubility in water being less than 1g / 100ml", it is particularly preferred that the ethylenically unsaturated monomer containing alicyclic structure.
[0033] In addition, as other nonionic ethylenically unsaturated monomers, for example, (meth)acrylates can be used. Examples of (meth)acrylates include alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; Aromatic (meth)acrylate compounds such as phenyl (meth)acrylate, phenyl methyl (meth)acrylate, phenyl ethyl (meth)acrylate, and phenoxyethyl (meth)acrylate; Alkoxyalkyl (meth)acrylate compounds such as 2-methoxyethyl (meth)acrylate and 2-ethoxyethyl (meth)acrylate, etc.; these may be used alone or in combination of two or more.
[0034] From the viewpoint of adhesion to the active material and cycle characteristics, aromatic (meth)acrylate compounds can be preferably used. From the viewpoint of further improving lithium ion conductivity and high rate characteristics, compounds having ether bonds are preferably used, and the compounds having ether bonds are (meth)acrylic acid alkoxyalkyl esters such as (meth)acrylate 2-methoxyethyl ester and (meth)acrylate 2-ethoxyethyl ester, and more preferably (meth)acrylate 2-methoxyethyl ester.
[0035] From the viewpoint of obtaining a polymer with a long primary chain length due to a fast polymerization rate and good adhesive strength of the adhesive, compounds having an acryloyl group are preferred among the nonionic ethylenically unsaturated monomers. In addition, from the viewpoint of good bending resistance of the obtained electrode, compounds having a homopolymer glass transition temperature (Tg) of 0°C or less are preferred as nonionic ethylenically unsaturated monomers.
[0036] The present cross-linked polymer is a cross-linked polymer having a cross-linked structure. The cross-linking method in the present cross-linked polymer is not particularly limited, and for example, the following method can be shown. 1) Copolymerization of a crosslinking monomer (however, different from the above-mentioned polyfunctional cationic group-containing compound) 2) Chain transfer to polymer chains during free radical polymerization The crosslinked polymer has a crosslinked structure, and thus, an adhesive containing the crosslinked polymer or a salt thereof can have excellent adhesive strength. Among the above, the method of copolymerizing a crosslinkable monomer is preferred from the viewpoint of easy operation and easy control of the degree of crosslinking.
[0037] <Crosslinking Monomer> Examples of the crosslinkable monomer include polyfunctional polymerizable monomers having two or more polymerizable unsaturated groups and monomers having self-crosslinkable crosslinkable functional groups such as hydrolyzable silyl groups, etc. However, this is different from the polyfunctional cationic group-containing compounds described above.
[0038] The above-mentioned multifunctional polymerizable monomer is a compound having two or more polymerizable functional groups in the molecule, wherein the polymerizable functional group is (meth) acryloyl, alkenyl, etc. The above-mentioned multifunctional polymerizable monomer can include multifunctional (meth) acryloyl compounds, multifunctional alkenyl compounds, compounds having both (meth) acryloyl and alkenyl, etc. With regard to these compounds, one kind can be used alone, or two or more kinds can be used in combination. Among them, from the viewpoint of easily obtaining a uniform cross-linked structure, a multifunctional alkenyl compound is preferred, and a multifunctional allyl ether compound having two or more allyl ether groups in the molecule is particularly preferred.
[0039] Examples of the polyfunctional (meth)acryloyl compound include di(meth)acrylates of diols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; poly(meth)acrylates such as tri(meth)acrylates and tetra(meth)acrylates of tri- or higher-valent polyols such as trimethylolpropane tri(meth)acrylate, trimethylolpropane ethylene oxide-modified tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; polyfunctional urethane (meth)acrylates such as difunctional urethane (meth)acrylate; and bisamides such as methylenebisacrylamide and hydroxyethylenebisacrylamide.
[0040] Examples of the polyfunctional alkenyl compound include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.
[0041] Examples of the compound having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0042] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include hydrolyzable silyl group-containing vinyl monomers, N-methoxyalkyl (meth) acrylamide, etc. These compounds may be used alone or in combination of two or more.
[0043] The vinyl monomer containing a hydrolyzable silyl group is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group. Examples thereof include: vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, and vinyl dimethyl methoxysilane; silyl-containing acrylic acid esters such as trimethoxysilyl propyl acrylate, triethoxysilyl propyl acrylate, and methyl dimethoxysilyl propyl acrylate; silyl-containing methacrylic acid esters such as trimethoxysilyl propyl methacrylate, triethoxysilyl propyl methacrylate, methyl dimethoxysilyl propyl methacrylate, and dimethyl methoxysilyl propyl methacrylate; silyl-containing vinyl ethers such as trimethoxysilyl propyl vinyl ether; silyl-containing vinyl esters such as trimethoxysilyl undecanoic acid vinyl ester, and the like.
[0044] In the case where the cross-linked polymer is a polymer obtained by crosslinking a crosslinking monomer, relative to the total amount of 100 parts by mass of the monomer (non-crosslinking monomer) other than the crosslinking monomer, the usage amount of the crosslinking monomer is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, more preferably 0.05 parts by mass or more and 3.0 parts by mass or less, more preferably 0.1 parts by mass or more and 2.0 parts by mass or less, further preferably 0.1 parts by mass or more and 1.7 parts by mass or less, and more preferably 0.5 parts by mass or more and 1.5 parts by mass or less. If the usage amount of the crosslinking monomer is more than 0.01 parts by mass, it is preferred from the viewpoint of better sedimentation stability of cohesiveness and electrode slurry. If it is less than 5.0 parts by mass, there is a tendency that the stability of precipitation polymerization or dispersion polymerization becomes higher.
[0045] For the same reason, the amount of the cross-linking monomer used is preferably from 0.001 mol% to 2.5 mol%, more preferably from 0.01 mol% to 2.0 mol%, further preferably from 0.05 mol% to 1.75 mol%, further preferably from 0.05 mol% to 1.5 mol%, and still further preferably from 0.1 mol% to 1.0 mol%, relative to the total amount of monomers other than the cross-linking monomer (non-cross-linking monomer).
[0046] The cross-linked polymer salt is a salt in which part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include: alkali metal salts such as lithium salts, sodium salts and potassium salts; alkaline earth metal salts such as magnesium salts, calcium salts and barium salts; other metal salts such as aluminum salts; ammonium salts and organic amine salts. Among them, alkali metal salts and alkaline earth metal salts are preferred, and alkali metal salts are more preferred, from the viewpoint of not easily adversely affecting battery characteristics.
[0047] About the properties of this cross-linked polymer salt Regarding the present cross-linked polymer, in the present composition, it is preferred to neutralize the acid groups such as carboxyl groups derived from the ethylenically unsaturated carboxylic acid monomers in a manner such that the neutralization degree is 20 mol% or more, and use it in the form of a salt. The above-mentioned neutralization degree is more preferably 50 mol% or more, further preferably 70 mol% or more, further preferably 75 mol% or more, further more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the neutralization degree is 100 mol%, and may be 98 mol%, and may be 95 mol%. In the case where the neutralization degree is 20 mol% or more, it is preferred from the viewpoint of good water swelling and easy dispersion stabilization effect. In this specification, the above-mentioned neutralization degree can be calculated by calculating the feeding value of the monomer having an acid group such as a carboxyl group and the neutralizing agent used for neutralization. In addition, the cross-linked polymer salt can be subjected to IR measurement of the powder after drying at 80°C for 3 hours under reduced pressure conditions, and the neutralization degree can be confirmed by the intensity ratio of the peak of the C=O group derived from the carboxylic acid and the peak of the C=O group derived from the carboxylate.
[0048] <Particle Size of the Cross-linked Polymer Salt> In the present composition, the present crosslinked polymer salt is preferably present as water-swellable particles having an appropriate particle size, rather than as large-diameter aggregates (secondary aggregates), because the adhesive containing the crosslinked polymer salt can exhibit good adhesive properties.
[0049] For the present cross-linked polymer, the particle size (water-swollen particle size) when a polymer having a neutralization degree of 80 mol% to 100 mol% based on the carboxyl group possessed by the cross-linked polymer is dispersed in water is preferably in the range of 0.1 μm to 10.0 μm in terms of volume-based median diameter. The more preferred range of the above particle size is 0.15 μm to 8.0 μm, the further preferred range is 0.20 μm to 6.0 μm, the further preferred range is 0.25 μm to 4.0 μm, and the further preferred range is 0.30 μm to 2.0 μm. If the particle size is in the range of 0.30 μm to 2.0 μm, it exists uniformly in the present composition with a suitable size, so the present composition has high stability and can exert excellent adhesion. If the particle size is greater than 10.0 μm, there is a risk that the adhesion becomes insufficient as described above. In addition, from the viewpoint of difficulty in obtaining a coating surface with smoothness, there is a risk that the coating property becomes insufficient. On the other hand, when the particle size is less than 0.1 μm, there is a concern from the viewpoint of stable manufacturability.
[0050] <Viscosity of Aqueous Solution of the Crosslinked Polymer Salt> The present cross-linked polymer salt preferably has a 2 mass % aqueous solution with a viscosity of 100 mPa·s or more. When the viscosity of the 2 mass % aqueous solution is 100 mPa·s or more, the composition containing the cross-linked polymer has high storage stability and can exhibit excellent adhesiveness. The viscosity of the 2 mass % aqueous solution may be 1,000 mPa·s or more, 10,000 mPa·s or more, or 50,000 mPa·s or more. The viscosity of the aqueous solution can be obtained by uniformly dissolving or dispersing the crosslinked polymer salt of the present invention in water in an amount to achieve a predetermined concentration, and then measuring the B-type viscosity (25° C.) at 12 rpm according to the method described in Examples.
[0051] This cross-linked polymer salt absorbs water in water and becomes a swollen state. Usually, when the cross-linked polymer has a moderate degree of cross-linking, the more the amount of hydrophilic groups possessed by the cross-linked polymer, the easier it is for the cross-linked polymer to absorb water and swell. In addition, for the degree of cross-linking, the lower the degree of cross-linking, the easier it is for the cross-linked polymer to swell. However, even if the number of cross-linking points is the same, the cross-linking points that contribute to the formation of a three-dimensional network increase because the molecular weight (primary chain length) is larger, so the cross-linked polymer becomes more difficult to swell. Therefore, the viscosity of the cross-linked polymer aqueous solution can be adjusted by adjusting the amount of hydrophilic groups of the cross-linked polymer, the number of cross-linking points and the primary chain length. At this time, the number of the above-mentioned cross-linking points can be adjusted, for example, by the amount of cross-linking monomers used, chain transfer reactions to polymer chains, and post-crosslinking reactions. In addition, the primary chain length of the polymer can be adjusted by setting the conditions related to the amount of free radical generation, such as initiator and polymerization temperature, and the selection of polymerization solvents taking into account chain transfer, etc.
[0052] <Water Swelling Degree of the Cross-linked Polymer Salt> In this specification, the weight of the cross-linked polymer salt when dried is referred to as "(W A )g" and the amount of water absorbed when the cross-linked polymer salt is saturated with water "(W B )g", the water swelling degree was calculated based on the following formula. (Water Swelling Degree) = {(W A )+(W B )} / (W A )
[0053] The water swelling degree of the cross-linked polymer salt at pH 8 is preferably 20 or more and 80 or less. If the water swelling degree is within the above range, the cross-linked polymer salt swells moderately in the aqueous medium, so when forming the electrode mixture layer, sufficient bonding area can be ensured for the active material and the collector, and there is a tendency for the bonding to become good. The above-mentioned water swelling degree can be, for example, 21 or more, 23 or more, 25 or more, 27 or more, or 30 or more. When the water swelling degree is 20 or more, the cross-linked polymer salt spreads on the surface of the active material and the collector, and sufficient bonding area can be ensured, so good bonding can be obtained. The upper limit of the water swelling degree at pH 8 can be 75 or less, 70 or less, 65 or less, 60 or less, or 55 or less. If the water swelling degree is greater than 60, there is a tendency for the viscosity of the electrode mixture layer composition (electrode slurry) containing the cross-linked polymer salt to increase, and the uniformity of the mixture layer is insufficient, resulting in the situation that sufficient bonding force cannot be obtained. In addition, there is a risk of reduced coating of the electrode slurry. The water swelling degree at pH 8 can be obtained by measuring the swelling degree of the cross-linked polymer salt in water at pH 8. As the water at pH 8, for example, ion exchange water can be used, and the pH value can be adjusted as needed using an appropriate acid or base, or a buffer solution. The pH during measurement is, for example, in the range of 8.0 ± 0.5, preferably in the range of 8.0 ± 0.3, more preferably in the range of 8.0 ± 0.2, and even more preferably in the range of 8.0 ± 0.1. In addition, the measurement is performed at 25 ± 5 ° C.
[0054] In addition, those skilled in the art can adjust the water swelling degree of the cross-linked polymer salt by controlling the composition and structure of the cross-linked polymer salt. For example, the water swelling degree can be increased by introducing an acidic functional group or a highly hydrophilic structural unit into the cross-linked polymer. In addition, by reducing the cross-linking degree of the cross-linked polymer, the water swelling degree thereof is generally increased.
[0055] 3. Method for producing the cross-linked polymer The cross-linked polymer can be prepared by known polymerization methods such as solution polymerization, precipitation polymerization, suspension polymerization, and emulsion polymerization. From the perspective of productivity, precipitation polymerization and suspension polymerization (reverse phase suspension polymerization) are preferred. Regarding adhesion, from the perspective of obtaining better performance, heterogeneous polymerization methods such as precipitation polymerization, suspension polymerization, and emulsion polymerization are preferred, and precipitation polymerization is more preferred. Precipitation polymerization is a method of producing a polymer by carrying out a polymerization reaction in a solvent, wherein the solvent is a solvent that dissolves the unsaturated monomer as a raw material but does not substantially dissolve the resulting polymer. As the polymerization proceeds, the polymer particles grow larger by aggregation and growth, and a dispersion liquid is obtained in which primary particles of tens to hundreds of nm are secondary aggregated into polymer particles of several to tens of μm. In order to control the particle size of the polymer, a dispersion stabilizer may also be used. In addition, the above-mentioned secondary aggregation can also be suppressed by selecting a dispersion stabilizer, a polymerization solvent, etc. Generally, precipitation polymerization in which secondary aggregation is suppressed is also called dispersion polymerization.
[0056] In the case of precipitation polymerization, the polymerization solvent may be selected from water and various organic solvents, etc., in consideration of the type of monomer used, etc. In order to obtain a polymer with a longer primary chain length, it is preferred to use a solvent with a small chain transfer constant.
[0057] As specific polymerization solvents, in addition to water-soluble solvents such as methanol, tert-butyl alcohol, acetone, methyl ethyl ketone, acetonitrile and tetrahydrofuran, benzene, ethyl acetate, ethylene dichloride, n-hexane, cyclohexane and n-heptane can also be cited, and one of them can be used alone or in combination of two or more. Alternatively, they can also be used as a mixed solvent with water. In the present invention, a water-soluble solvent means a solvent whose solubility in water at 20° C. is greater than 10 g / 100 ml. Among the above, methyl ethyl ketone and acetonitrile are preferred from the viewpoints of less generation of coarse particles and less adhesion to the reactor, good polymerization stability, less likelihood of secondary aggregation of precipitated polymer microparticles (or easy loosening in an aqueous medium even if secondary aggregation occurs), the ability to obtain a polymer having a small chain transfer constant and a large degree of polymerization (primary chain length), and easy handling during neutralization in the steps described later.
[0058] The polymerization initiator can use known polymerization initiators such as azo compounds, organic peroxides, inorganic peroxides, etc., without particular limitation. The use conditions can be adjusted by using known methods such as thermal initiation, redox initiation of reducing agents, UV initiation, etc., so as to reach a suitable free radical generation amount. In order to obtain a cross-linked polymer with a long primary chain length, it is preferred to set conditions within the scope allowed by the manufacturing time so that the free radical generation amount is further reduced.
[0059] When the total amount of the monomer components used is set to 100 parts by mass, the preferred amount of the polymerization initiator used is, for example, 0.001 to 2 parts by mass, and for example, 0.005 to 1 part by mass, and for example, 0.01 to 0.1 parts by mass. If the amount of the polymerization initiator used is 0.001 parts by mass or more, the polymerization reaction can be stably carried out, and if it is 2 parts by mass or less, a polymer with a long primary chain length is easily obtained.
[0060] The polymerization temperature also depends on the type and concentration of the monomers used, and is preferably 0° C. to 100° C., and more preferably 20° C. to 80° C. The polymerization temperature may be fixed or may be varied during the polymerization reaction. In addition, the polymerization time is preferably 1 minute to 20 hours, and more preferably 1 hour to 10 hours.
[0061] Here, the present cross-linked polymer may contain 50% by mass or more and 100% by mass or less of an ethylenically unsaturated carboxylic acid monomer. The types of the ethylenically unsaturated carboxylic acid monomer are as described above.
[0062] 4. Composition for secondary battery electrode mixture layer The composition for a secondary battery electrode mixture layer of the present invention comprises the present binder, a polyfunctional cationic group-containing compound, an active material and water. Relative to the total amount of 100 parts by mass of active material, the usage amount of this adhesive in this composition is, for example, more than 0.1 parts by mass and less than 20 parts by mass. The above usage amount is, for example, more than 0.2 parts by mass and less than 10 parts by mass, and for example, more than 0.3 parts by mass and less than 8 parts by mass, and for example, more than 0.4 parts by mass and less than 5 parts by mass. If the usage amount of adhesive is more than 0.1 parts by mass, sufficient adhesion can be obtained. In addition, the dispersion stability of active materials etc. can be ensured, and a uniform composite layer can be formed. If the usage amount of adhesive is less than 20 parts by mass, this composition will not become high viscosity, and the coating property to the collector can be ensured. As a result, a composite layer with a uniform and smooth surface can be formed.
[0063] Relative to the total amount of 100 parts by mass of this adhesive, the amount of the polyfunctional cationic group-containing compound in this composition is, for example, 0.1 parts by mass or more and 20 parts by mass or less. The above-mentioned amount is, for example, 0.5 parts by mass or more and 15 parts by mass or less, and for example, 1.0 parts by mass or more and 10 parts by mass or less, and for example, 2.0 parts by mass or more and 8 parts by mass or less. In particular, if the amount of the polyfunctional cationic group-containing compound is 0.1 parts by mass or more, the cross-linked structure between the cross-linked polymer is fully formed by the reaction of the carboxyl group in this cross-linked polymer with the polyfunctional cationic group-containing compound, and the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery can be improved. In addition, if the amount of the polyfunctional cationic group-containing compound is 20 parts by mass or less, the amount of the unreacted polyfunctional cationic group-containing compound is reduced, and the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery can be improved.
[0064] In addition, from the viewpoint of being able to exert the toughness of the adhesive coating after electrolyte immersion, the electrolyte resistance of the secondary battery electrode mixture layer, and the cycle characteristics of the secondary battery, the molar ratio of the cationic group to the carboxyl group in the present adhesive is preferably 0.05 mol or more and 3.0 mol or less, more preferably 0.1 mol or more and 2.5 mol or less, further preferably 0.2 mol or more and 2.0 mol or less, further preferably 0.3 mol or more and 1.5 mol or less, further more preferably 0.5 mol or more and 1.3 mol or less, and further more preferably 0.7 mol or more and 1.0 mol or less.
[0065] Among the above active materials, lithium salts of transition metal oxides can be used as positive electrode active materials, for example, layered rock salt type and spinel type lithium-containing metal oxides can be used. Specific compounds of layered rock salt type positive electrode active materials include lithium cobalt oxide, lithium nickel oxide, and NCM {Li(Ni x ,Co y ,Mn z ), x+y+z=1} and NCA{Li(Ni 1-a-b Co a Al b )}, etc. In addition, as a spinel-type positive electrode active material, lithium manganate, etc. can be cited. In addition to oxides, phosphates, silicates and sulfur, etc. are also used; as phosphates, olivine-type lithium iron phosphate, etc. can be cited. As a positive electrode active material, one of the above can be used alone, or two or more can be combined as a mixture or a composite.
[0066] In addition, when the positive electrode active material containing a layered rock salt type lithium metal oxide is dispersed in water, the lithium ions on the surface of the active material are exchanged with the hydrogen ions in the water, whereby the dispersion shows alkalinity. Therefore, there is a risk of corrosion of the usual positive electrode collector material, i.e., aluminum foil (Al), etc. In such a case, it is preferred that the unneutralized or partially neutralized cross-linked polymer is used as a binder to neutralize the alkali component dissolved from the active material. In addition, the amount of the unneutralized or partially neutralized cross-linked polymer used is preferably used in a manner that the amount of unneutralized carboxyl groups of the cross-linked polymer is equivalent to or more than the amount of alkali dissolved from the active material.
[0067] The electrical conductivity of the positive electrode active material is low, so a conductive aid is usually added for use. As a conductive aid, carbon materials such as carbon black, carbon nanotubes, carbon fibers, graphite powder, and carbon fibers (carbon fibers) can be cited, among which, from the viewpoint of easily obtaining excellent conductivity, carbon black, carbon nanotubes, and carbon fibers are preferably used. In addition, as carbon black, Ketjen black and acetylene black are preferably used. The conductive aid can be used alone or in combination with two or more of the above. From the viewpoint of taking into account both conductivity and energy density, the amount of the conductive aid used can be, for example, 0.2 to 20 parts by mass relative to the total amount of 100 parts by mass of the active material, and, for example, can be set to 0.2 to 10 parts by mass. In addition, the positive electrode active material can use a material coated with a conductive carbon material.
[0068] On the other hand, as the negative electrode active material, for example, carbon-based materials, lithium metal, lithium alloys and metal oxides can be cited, and one of them or a combination of two or more thereof can be used. Among them, an active material composed of carbon-based materials such as natural graphite, artificial graphite, hard carbon and soft carbon (hereinafter also referred to as "carbon-based active material") is preferred, and graphite such as natural graphite and artificial graphite, and hard carbon are more preferred. In addition, in the case of graphite, from the perspective of battery performance, spheroidized graphite is preferably used, and the preferred range of its particle size is, for example, 1 μm to 20 μm, and, for example, 5 μm to 15 μm. In addition, in order to improve the energy density, metals or metal oxides such as silicon and tin that can absorb lithium can also be used as negative electrode active materials. Among them, silicon has a higher capacity than graphite, and an active material composed of silicon-based materials such as silicon, silicon alloys and silicon oxides such as silicon monoxide (SiO) (hereinafter also referred to as "silicon-based active materials") can be used. However, although the above-mentioned silicon-based active materials have a high capacity, on the other hand, the volume change accompanying charging and discharging is large. Therefore, it is preferably used in combination with the above-mentioned carbon-based active material. In this case, if the amount of silicon-based active material is large, it will cause the collapse of the electrode material, and there is a situation where the cycle characteristics (durability) are greatly reduced. From this point of view, when the silicon-based active material is used in combination, its usage amount is, for example, 60% by mass or less relative to the carbon-based active material, and, for example, 30% by mass or less.
[0069] The carbon-based active material itself has good electrical conductivity, so it is not necessary to add a conductive aid. In the case of adding a conductive aid for the purpose of further reducing resistance, from the viewpoint of energy density, the amount used is, for example, 10 parts by mass or less, and, for example, 5 parts by mass or less relative to 100 parts by mass of the total amount of the active material.
[0070] When the present composition is in a slurry state, the amount of the active material used is, for example, in the range of 10% to 75% by mass, or, for example, in the range of 30% to 65% by mass, relative to the total amount of the present composition. If the amount of the active material used is 10% by mass or more, it is also advantageous in terms of the drying cost of the medium while suppressing the migration of the adhesive, etc. On the other hand, if it is 75% by mass or less, the fluidity and coating properties of the present composition can be ensured, and a uniform mixture layer can be formed.
[0071] This composition uses water as a medium. In addition, for the purpose of adjusting the properties and dryness of this composition, a mixed solvent of a water-soluble organic solvent such as lower alcohols such as methanol and ethanol, carbonates such as ethylene carbonate, ketones such as acetone, tetrahydrofuran, N-methyl-2-pyrrolidone, etc. can be used. The proportion of water in the mixed medium is, for example, 50% by mass or more, and, for example, 70% by mass or more.
[0072] When the present composition is made into a coatable slurry state, the content of the medium including water in the entire composition can be set to, for example, a range of 25 mass % to 60 mass %, and can be, for example, 35 mass % to 60 mass %, from the viewpoint of the coatability of the slurry, the energy cost required for drying, and productivity.
[0073] This composition can also be used in combination with other adhesive components such as styrene butadiene rubber (SBR) latex, carboxymethyl cellulose (CMC), acrylic latex and polyvinylidene fluoride latex. In the case of using other adhesive components, its usage amount can be set to, for example, 0.1 mass part to 5 mass parts or less relative to the total amount 100 mass parts of active material, in addition, for example, it can be set to 0.1 mass part to 2 mass parts or less, in addition, for example, it can be set to 0.1 mass part to 1 mass part or less. If the usage amount of other adhesive components is greater than 5 mass parts, the resistance increases, and there is a situation where high-rate characteristics are insufficient. From the viewpoint of excellent balance between cohesiveness and bending resistance, preferably SBR latex, CMC, more preferably SBR latex and CMC are used in combination.
[0074] The above-mentioned SBR latex refers to an aqueous dispersion of a copolymer having a structural unit derived from an aromatic vinyl monomer such as styrene and a structural unit derived from an aliphatic conjugated diene monomer such as 1,3-butadiene. As the above-mentioned aromatic vinyl monomer, in addition to styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. can also be mentioned, and one or more of them can be used. Mainly from the viewpoint of adhesion, the structural unit derived from the above-mentioned aromatic vinyl monomer in the above-mentioned copolymer can be set to a range of, for example, 20% to 70% by mass, and can also be set to a range of, for example, 30% to 60% by mass. As the above-mentioned aliphatic conjugated diene monomer, for example, in addition to 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, etc. can also be cited, and one or more of them can be used. In terms of good adhesion of the binder and the flexibility of the obtained electrode, the structural unit derived from the above-mentioned aliphatic conjugated diene monomer in the above-mentioned copolymer can be set to a range of, for example, 30% to 70% by mass, and can also be set to a range of, for example, 40% to 60% by mass. In order to further improve the properties such as adhesion, in addition to the above-mentioned monomers, styrene / butadiene latex can also use the following monomers as other monomers and used as copolymer monomers: (meth) acrylonitrile and other nitrile-containing monomers; (meth) acrylic acid, itaconic acid, maleic acid and other carboxyl-containing monomers; (meth) methyl (meth) acrylate and other ester-containing monomers. The content of the structural unit derived from the other monomer in the copolymer can be, for example, in the range of 0% by mass to 30% by mass, and can also be, for example, in the range of 0% by mass to 20% by mass.
[0075] The above-mentioned CMC represents a nonionic cellulose-based semisynthetic polymer compound substituted with a carboxymethyl group and a salt thereof. Examples of the above-mentioned nonionic cellulose-based semisynthetic polymer compound include alkyl celluloses such as methyl cellulose, methylethyl cellulose, ethyl cellulose, and microcrystalline cellulose; hydroxyethyl cellulose, hydroxybutyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose stearyl ether, carboxymethyl hydroxyethyl cellulose, alkyl hydroxyethyl cellulose, and nonylphenol polyether hydroxyethyl cellulose.
[0076] The secondary battery electrode mixture layer composition of the present invention is composed of the above-mentioned binder, multifunctional compound containing cationic groups, active material and water as necessary components, and can be obtained by mixing the components using known means. The mixing method of each component is not particularly limited, and known methods can be used, but it is preferred to dry-mix the powder components such as active material, conductive aid and binder and mix them with a dispersion medium such as water for dispersion and kneading. In the case of obtaining the present composition in a slurry state, it is preferably processed into a slurry without poor dispersion and coagulation. As a mixing means, a planetary mixer, a thin film rotary mixer and a self-revolution mixer and other known mixers can be used. From the viewpoint of obtaining a good dispersion state in a short time, it is preferably carried out using a thin film rotary mixer. In addition, when a thin film rotary mixer is used, it is preferably pre-dispersed in a mixer such as a disperser (ディスパー). As long as the effect of the present invention is achieved, the pH of the slurry is not particularly limited, and is preferably less than 12.5. For example, in the case of mixing CMC, it is more preferably less than 11.5, and further preferably less than 10.5 from the viewpoint of less concern about its hydrolysis. In addition, as long as the effect of the present invention is achieved, the viscosity of the slurry is not particularly limited, and as a B-type viscosity (25°C) at 20 rpm, for example, it can be set to a range of 100 mPa·s to 6,000 mPa·s, and for example, it can be set to 500 mPa·s to 5,000 mPa·s, and for example, it can be set to a range of 1,000 mPa·s to 4,000 mPa·s. If the viscosity of the slurry is within the above range, good coating properties can be ensured.
[0077] 5. Secondary battery electrodes The secondary battery electrode of the present invention is an electrode having a mixture layer formed by the composition for the secondary battery electrode mixture layer of the present invention on the surface of a current collector such as copper or aluminum. The mixture layer can be formed by drying and removing media such as water after applying the composition on the surface of the current collector. The method for applying the composition is not particularly limited, and known methods such as a doctor blade method, a dipping method, a roller coating method, a comma coating method, a curtain coating method, a gravure coating method, and an extrusion method can be used. In addition, the above-mentioned drying can be carried out by known methods such as warm wind blowing, decompression, (far) infrared rays, microwave irradiation, etc. Usually, the composite layer obtained after drying is subjected to compression treatment such as die stamping and roller pressing. By compressing the active material and the binder to be in close contact, the strength of the composite layer and the adhesion to the collector can be improved. By compression, for example, the thickness of the composite layer can be adjusted to about 30% to 80% of that before compression, and the thickness of the composite layer after compression is usually about 4 μm to 200 μm.
[0078] 6. Secondary batteries The secondary battery electrode of the present invention is provided with a separator and an electrolyte, so that a secondary battery can be produced. The electrolyte may be in a liquid state or in a gel state. The separator is arranged between the positive electrode and the negative electrode of the battery, and is responsible for preventing the short circuit caused by the contact between the two electrodes, maintaining the electrolyte and ensuring the ionic conductivity. For the separator, it is preferred to have a film-like insulating microporous film with good ion permeability and mechanical strength. As specific raw materials, polyolefins such as polyethylene and polypropylene, polytetrafluoroethylene, etc. can be used.
[0079] Regarding the electrolyte, commonly used known electrolytes can be used according to the type of active material. In lithium-ion secondary batteries, specific solvents include: cyclic carbonates with high dielectric constants and high electrolyte solubility such as propylene carbonate and ethylene carbonate; and chain carbonates with low viscosity such as ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate; these can be used alone or as a mixed solvent. Dissolve LiPF in these solvents 6 、LiSbF 6 , LiBF 4 、LiClO 4 、LiAlO 4 A lithium salt such as iodine is used as an electrolyte. In nickel-hydrogen secondary batteries, potassium hydroxide aqueous solution can be used as an electrolyte. A secondary battery can be obtained by making a positive electrode plate and a negative electrode plate separated by a separator into a roll or a stacked structure and accommodating them in a housing or the like.
[0080] The adhesive for secondary battery electrodes disclosed in this specification has excellent toughness of the adhesive coating after electrolyte impregnation, and the secondary battery electrode mixed material layer obtained by using the electrode slurry containing the adhesive also shows electrolyte resistance. Furthermore, the secondary battery with the electrode obtained by using the above-mentioned adhesive can ensure good integrity, and even if it is repeatedly charged and discharged, it also shows good durability (cycle characteristics), so it is suitable for vehicle-mounted secondary batteries, etc. Example
[0081] Hereinafter, the present invention will be specifically described based on examples. In addition, the present invention is not limited to these examples. In addition, the following "parts" and "%" mean parts by mass and mass % unless otherwise specified. In the following examples, evaluation of the carboxyl group-containing polymer salt was carried out by the following method.
[0082] 《Manufacturing of carboxyl-containing polymer salts》 (Measurement of particle size in aqueous medium (water-swollen particle size)) 0.25 g of the powder of the carboxyl-containing cross-linked polymer salt and 49.75 g of ion exchange water were weighed into a 100 cc container and placed in a rotation / revolution type mixer (manufactured by Shinki Co., Ltd., Awato Ri Rentaro AR-250). Then, stirring was performed (rotation speed 2,000 rpm / revolution speed 800 rpm, 7 minutes), and further degassing (rotation speed 2,200 rpm / revolution speed 60 rpm, 1 minute) treatment was performed to obtain a hydrogel in a state where the carboxyl-containing cross-linked polymer salt was swollen in water. Next, the particle size distribution of the hydrogel is measured by a laser diffraction / scattering particle size distribution meter (manufactured by Microtrac Bell, Microtrac MT-3300EXII) using ion exchange water as a dispersion medium. When the dispersion medium in excess relative to the hydrogel is circulated, the hydrogel in an amount that can obtain an appropriate scattered light intensity is added, and the particle size distribution shape measured after a few minutes is stable. Once stability is confirmed, the particle size distribution is measured immediately to obtain a volume-based median diameter (D50) as a representative value of the particle size.
[0083] (Production Example 1: Production of Carboxyl Group-Containing Crosslinked Polymer Salt R-1) In the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux cooler and a nitrogen inlet pipe was used. In the reactor, 567 parts of acetonitrile, 2.2 parts of ion exchange water, 100 parts of acrylic acid (hereinafter referred to as "AA"), 0.9 parts of trimethylolpropane diallyl ether (manufactured by Osaka Soda Co., Ltd., trade name "Neoariel T-20") and 1.0 mol% of triethylamine were added. After the reactor was fully substituted with nitrogen, the internal temperature was heated to 55°C. After confirming that the internal temperature was stable at 55°C, 0.040 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm and Kou Junyao Co., Ltd., trade name "V-65") as a polymerization initiator was added. As a result, white turbidity was confirmed in the reaction solution, so this point was used as the polymerization start point. In addition, the monomer concentration was calculated to be 15%. The polymerization reaction solution was cooled 12 hours after the polymerization start point, and after the internal temperature dropped to 25° C., lithium hydroxide monohydrate (hereinafter referred to as “LiOH·H 2 After the addition, stirring was continued at room temperature for 12 hours to obtain a slurry-like polymerization reaction liquid in which particles of carboxyl-containing cross-linked polymer salt R-1 (lithium salt, neutralization degree 90 mol%) were dispersed in a medium.
[0084] The obtained polymerization reaction liquid is centrifuged to precipitate the polymer and remove the supernatant. After that, the washing operation of redispersing the precipitate in acetonitrile of the same weight as the polymerization reaction liquid and then centrifuging the polymer particles to precipitate and remove the supernatant is repeated twice. The precipitate is recovered and the volatile components are removed by drying at 80°C for 3 hours under reduced pressure to obtain a powder of the carboxyl-containing cross-linked polymer salt R-1. Since the carboxyl-containing cross-linked polymer salt R-1 is hygroscopic, it is sealed and stored in a container with water vapor barrier properties. In addition, the powder of the carboxyl-containing cross-linked polymer salt R-1 is subjected to IR measurement, and the neutralization degree is calculated by the intensity ratio of the peak of the C=O group from the carboxylic acid to the peak of the C=O group from the lithium carboxylate. The result is equal to the calculated value based on the feed, which is 90 mol%. In addition, the particle size in the aqueous medium is 1.52 μm.
[0085] (Manufacturing Examples 2 to 7 and Comparative Manufacturing Example 1: Manufacture of Carboxyl-Containing Crosslinked Polymer Salts R-2 to R-7 and Carboxyl-Containing Non-Crosslinked Polymer Salt R-8) Except that the types and feed amounts of each raw material are set as described in Table 1, the same operations as in Production Example 1 are carried out to obtain a polymerization reaction liquid containing carboxyl-containing cross-linked polymer salts R-2 to R-7 and carboxyl-containing non-cross-linked polymer salt R-8. Next, each polymerization reaction solution was subjected to the same operation as in Production Example 1 to obtain powdered carboxyl group-containing crosslinked polymer salts R-2 to R-7 and carboxyl group-containing non-crosslinked polymer salt R-8. Each polymer salt was sealed and stored in a container having water vapor barrier properties. The physical property values of each polymer salt obtained were measured in the same manner as in Production Example 1. The results are shown in Table 1.
[0086] [Table 1]
[0087] The details of the compounds used in Table 1 are shown below. AA: Acrylic acid HEAA: N-Hydroxyethylacrylamide ·T-20: trimethylolpropane diallyl ether (manufactured by Osaka Soda Co., Ltd., trade name "Neoall T-20") ·UN-6200: Bifunctional urethane acrylate (manufactured by Negami Industries, trade name "Artilesin UN-6200") ·TEA: Triethylamine · V-65: 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, trade name "V-65") ·LiOH·H 2 O: Lithium hydroxide monohydrate ·Na 2 CO 3 :Sodium carbonate ·K 2 CO 3 :Potassium carbonate
[0088] Example 1 (Production of Adhesive Coating Film) The carboxyl-containing cross-linked polymer salt R-1, styrene / butadiene latex (SBR), sodium carboxymethylcellulose (CMC), polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., trade name "EPOMIN SP-200", weight average molecular weight 10,000, hereinafter also referred to as "PEI-1") and ion-exchanged water were added to a container and mixed in the parts listed in Table 2. After pre-dispersion by a disperser, a thin film rotary mixer (manufactured by Surface Mix Co., Ltd., FM-56-30) was used to perform formal dispersion for 15 seconds at a peripheral speed of 20 m / sec to obtain an aqueous binder solution. Then, the above-mentioned binder aqueous solution was poured into a tray, dried at 40° C. for 20 hours, and further vacuum-dried at 80° C. for 12 hours. The adhesive coating obtained after drying was punched out into a size of 1.0 cm×6.0 cm to prepare a test piece, and the toughness and electrolyte resistance were measured.
[0089] (Toughness of adhesive coating) The test piece punched out from the adhesive coating film was subjected to a tensile test at a speed of 10 mm / min using a tensile tester (RTC-1210A manufactured by Tensilon Orientec Corporation) to measure the Young's modulus [GPa]. The result was that the Young's modulus was 1.76 GPa. The test piece used for the evaluation of the swelling property of the electrolyte solution was also subjected to a tensile test under the same conditions to measure the Young's modulus. As a result, the Young's modulus was 1.47 GPa, and the toughness evaluation based on the following criteria was "A". In addition, the higher the Young's modulus of the binder coating after immersion in the electrolyte solution, the more excellent the toughness of the electrode mixture material layer is, and the cycle characteristics can be improved. (Criteria for judging toughness) A: Young's modulus after electrolyte immersion is 1.30 GPa or more B: Young's modulus after immersion in electrolyte is 1.20 GPa or more and less than 1.30 GPa C: Young's modulus after electrolyte immersion is less than 1.20 GPa
[0090] (Electrolyte resistance of adhesive coating) The test piece obtained above was immersed in an electrolyte solution mixed with ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:3 and left at 40° C. for 2 hours. The test piece was then taken out of the electrolyte solution, the surface was wiped, and the degree of swelling in the electrolyte solution was measured.
[0091] Here, the method for measuring the degree of swelling of the electrolyte solution is described below. The weights of the test pieces before and after immersion in the electrolyte were [W 0 (g)]、[W 1 (g)], and the electrolyte swelling degree was calculated by the following formula. Electrolyte swelling degree (mass %) = (W 1 ) / (W 0 )×100 According to the above formula, the electrolyte solution swelling property was 110%, and the electrolyte solution resistance evaluation based on the following criteria was "A". In addition, the lower the electrolyte swelling degree of the binder coating film is, the less likely it is for the electrode mixture material layer to absorb electrolyte components and the less likely it is for the electrode mixture material layer to swell in the electrolyte. (Criteria for judging electrolyte resistance) A: The electrolyte swelling degree is less than 111% B: Electrolyte swelling degree is 111% or more and less than 116% C: Electrolyte swelling degree is 116% or more and less than 121% D: Electrolyte swelling degree is more than 121%
[0092] Examples 2 to 13, and Comparative Examples 1 to 2 The same operation as in Example 1 was carried out except that the compounding ratio was set as described in Table 2 to prepare an adhesive coating film, and the toughness and electrolyte resistance were evaluated.
[0093] Example 1 (Preparation of composition for electrode mixture layer) Artificial graphite (manufactured by Showa Denko Co., Ltd., trade name "SCMG-CF") and SiO (manufactured by Osaka Chitanium Technologies Co., Ltd., 5 μm) were used as active materials. A mixture of carboxyl-containing cross-linked polymer salt R-1, styrene / butadiene rubber (SBR) and sodium carboxymethylcellulose (CMC) was used as a binder. In addition, polyethyleneimine (PEI-1) was used as a polyfunctional cationic group-containing compound. In a planetary mixer (manufactured by Plaimics Companimics 2P-03 model), water was used as a diluent, and graphite: Si-based active material: R-1: SBR: CMC: PEI were added in a mass ratio of 76.8: 19.2: 1.0: 2.0: 1.0: 0.05 (solid content) so that the solid content concentration of the composition for the electrode mixture layer was 53% by mass. The mixture was mixed for 1 hour and 30 minutes to prepare a slurry-state composition for the electrode mixture layer (electrode slurry).
[0094] (Manufacturing of negative electrode plate) Next, the electrode slurry was applied to a collector (copper foil) with a thickness of 16.5 μm using a variable coater and dried in a ventilation dryer at 80°C for 15 minutes to form a composite layer. Then, the composite layer was rolled to a thickness of 50 ± 5 μm and a composite density of 1.60 ± 0.10 g / cm 3 Then, the sheet was punched into a size of 1.0 cm×6.0 cm for a peel strength test and a size of 3 cm square for battery evaluation to obtain a negative electrode plate.
[0095] (Production of positive electrode plate) LiNi as the positive electrode active material was mixed and added to N-methylpyrrolidone (NMP) solvent. 0.5 Co 0.2 Mn 0.3 O 2 100 parts of (NCM), 2 parts of acetylene black, and 4 parts of polyvinylidene fluoride (PVDF) as a positive electrode binder were mixed to prepare a positive electrode mixed material layer composition. The positive electrode mixed material layer composition was applied and dried on an aluminum current collector (thickness: 20 μm) to form a mixed material layer. After that, the mixed material layer was rolled to a thickness of 125 μm and a mixed material density of 3.0 g / cm 3 Then, it was punched into 3 cm squares to obtain the positive electrode plate.
[0096] (Preparation of Electrolyte) To a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio EC:DMC=3:7), 1 mass % of vinylene carbonate (VC) and 2 mass % of fluoroethylene carbonate (FEC) were added to dissolve LiPF at 1.2 mol / L. 6 , prepare a non-aqueous electrolyte.
[0097] (Manufacturing of Secondary Batteries) The structure of the battery is as follows: lead terminals are installed on the positive and negative electrodes respectively, and the electrode bodies facing each other through a diaphragm (made of polyethylene: film thickness 16μm, porosity 47%) are placed in a material using an aluminum laminate as the battery outer body for liquid injection, and then sealed as a test battery. In addition, the design capacity of this trial battery is 50mAh. As the design capacity of the battery, it is designed based on the charge termination voltage of 4.2V.
[0098] <Evaluation of Cycle Characteristics> The laminated lithium ion secondary battery prepared above was charged and discharged at a charge and discharge rate of 0.1C under the conditions of 2.5V to 4.2V by CC discharge at 45°C to measure the initial capacity C 0 Furthermore, the capacity C after 100 cycles was measured by repeatedly charging and discharging at a charge and discharge rate of 0.5 C under the condition of 2.5 V to 4.2 V by CC discharge at 25°C. 100 . Here, the cycle characteristic (ΔC) is obtained by the following formula. ΔC=C 100 / C 0 ×100(%) ΔC calculated from the above formula was 86.4%, and the cycle characteristics based on the following criteria were evaluated as "A". In addition, a higher ΔC value indicates better cycle characteristics. (Cycle Characteristics Criteria) A: The charge and discharge capacity retention rate is above 86.0% B: The charge and discharge capacity retention rate is 85.0% or more and less than 86.0% C: The charge and discharge capacity retention rate is 84.0% or more and less than 85.0% D: Charge and discharge capacity retention rate is less than 84.0%
[0099] Examples 2 to 13 and Comparative Examples 1 to 2 The electrode slurry was prepared in the same manner as in Example 1 except that the compounding ratio was set as described in Table 2, and the cycle characteristics of the battery of the negative electrode plate obtained using the electrode slurry were evaluated. The results are shown in Table 2.
[0100] [Table 2]
[0101] The details of the compounds used in Table 2 are shown below. CMC: Sodium Carboxymethyl Cellulose SBR: Styrene Butadiene Rubber PEI-1: Polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., trade name "Epomin SP-200", number average molecular weight according to boiling point rise method: 10,000) PEI-2: Polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., trade name "Epomin SP-006", number average molecular weight according to boiling point rise method: 600) PEI-3: Polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., trade name "Epomin P-1000", number average molecular weight according to the viscosity method is 70,000) PEDA: polyoxypropylene diamine (manufactured by HUNTSMAN, trade name "JEFFAMNINE D-400", weight average molecular weight according to the GPC method is 430) PETA: trimethylolpropane poly(oxypropylene) triamine (manufactured by HUNTSMAN, trade name "JEFFAMNINE T-403", weight average molecular weight according to the GPC method is 440)
[0102] 《Evaluation Results》 It can be seen from the results of Examples 1 to 13 that, regarding the adhesive for secondary battery electrodes of the present invention, the adhesive coating after impregnation with the electrolyte has excellent toughness; regarding the composition for secondary battery electrode mixture layer (electrode slurry) containing the adhesive for secondary battery electrodes of the present invention, the secondary battery electrode mixture layer has excellent electrolyte resistance and secondary battery cycle characteristics. Among them, if we focus on the molecular weight of the polyfunctional cationic group-containing compound, the cycle characteristics of the secondary battery are excellent when the molecular weight is 10,000 (Example 1) compared with the case where the molecular weight of the compound is 70,000 (Example 3) and the case where the molecular weight is 600 (Example 2). This is presumably because when a polyfunctional cationic group-containing compound having a molecular weight of 70,000 is used, the dispersion stability of the active material in the electrode slurry is impaired, and when a polyfunctional cationic group-containing compound having a molecular weight of 600 is used, crosslinking between binders is insufficient. Furthermore, as a polyfunctional compound containing cationic groups, when the molar ratio of the cationic group to the carboxyl group of the cross-linked polymer is in the range of 0.84 to 1.3 (Example 1, Example 4), the electrolyte resistance of the secondary battery electrode mixture layer and the cycle characteristics of the secondary battery are more excellent than when the molar ratio is in the range of 0.17 to 0.34 (Example 5, Example 12 and Example 13).
[0103] On the other hand, when the polyfunctional cationic group-containing compound was not contained, the toughness, electrolyte resistance and cycle characteristics of the adhesive coating film were all poor (Comparative Example 1). In addition, the toughness, electrolyte resistance and cycle characteristics of the adhesive coating film were significantly inferior when a non-crosslinked polymer salt containing a carboxyl group was used, compared with the case of using a crosslinked polymer salt containing a carboxyl group (Comparative Example 2). Industrial Applicability
[0104] The binder for secondary battery electrodes disclosed in the present specification has excellent toughness of the binder coating film after being impregnated with an electrolyte solution, and a secondary battery electrode mixture layer obtained by using an electrode slurry containing the binder exhibits electrolyte solution resistance. Furthermore, a secondary battery including an electrode obtained using the above binder can ensure good integrity and show good durability (cycle characteristics) even after repeated charge and discharge, and is therefore expected to contribute to higher capacity of in-vehicle secondary batteries and the like. The binder for secondary battery electrodes of the present invention is particularly suitable for non-aqueous electrolyte secondary battery electrodes, and is particularly useful for non-aqueous electrolyte lithium ion secondary batteries having a high energy density.
Claims
1. A binder for secondary battery electrodes, the binder for secondary battery electrodes being a binder for secondary battery electrodes containing a cross-linked polymer containing a carboxyl group or a salt thereof, wherein: At least a part of the carboxyl group is a functional group for bonding with an organic compound, and the organic compound is an organic compound having two or more cationic groups.
2. The binder for secondary battery electrodes according to claim 1, wherein The binder for secondary battery electrodes further contains an organic compound having two or more cationic groups, wherein the cationic groups are reactive with carboxyl groups (hereinafter referred to as "polyfunctional cationic group-containing compound").
3. The binder for secondary battery electrodes according to claim 2, wherein The polyfunctional cationic group-containing compound is contained so that the molar ratio of the cationic group to the carboxyl group of the cross-linked polymer is 0.05 or more and 3.0 or less.
4. The binder for secondary battery electrodes according to claim 2, wherein The molecular weight of the polyfunctional cationic group-containing compound is 300 or more and 100,000 or less.
5. The binder for secondary battery electrodes according to claim 3, wherein The molecular weight of the polyfunctional cationic group-containing compound is 300 or more and 100,000 or less.
6. The binder for secondary battery electrodes according to any one of claims 2 to 5, wherein The polyfunctional cationic group-containing compound contains at least one selected from the group consisting of polyethyleneimine, polyethyleneimine derivatives and polyetheramines.
7. The binder for secondary battery electrodes according to claim 1, wherein The carboxyl group-containing crosslinked polymer contains 50% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof.
8. The binder for secondary battery electrodes according to claim 6, wherein The carboxyl group-containing crosslinked polymer contains 50% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof.
9. The binder for secondary battery electrodes according to claim 6, wherein The cross-linked polymer is a cross-linked polymer obtained by polymerizing a monomer composition containing a non-cross-linking monomer and a cross-linking monomer (but different from the polyfunctional cationic group-containing compound).
10. The binder for secondary battery electrodes according to claim 9, wherein The amount of the crosslinkable monomer used is 0.001 mol % or more and 2.5 mol % or less relative to the total amount of the non-crosslinkable monomer.
11. The binder for secondary battery electrodes according to claim 1, wherein After the cross-linked polymer is neutralized to a degree of neutralization of 80 mol % to 100 mol %, the particle size measured in an aqueous medium is 0.1 μm or more and 10.0 μm or less in terms of volume-based median diameter.
12. The binder for secondary battery electrodes according to claim 6, wherein After the cross-linked polymer is neutralized to a degree of neutralization of 80 mol% to 100 mol%, the particle size measured in an aqueous medium is 0.1 μm or more and 10.0 μm or less in terms of volume-based median diameter.
13. A composition for a secondary battery electrode mixture layer, wherein: The composition for a secondary battery electrode mixture layer contains the binder for secondary battery electrodes according to claim 6, an active material, and water.
14. The composition for a secondary battery electrode mixture layer according to claim 13, wherein The active material contains a silicon-based active material.
15. A secondary battery electrode, wherein: The secondary battery electrode comprises a mixture layer formed from the composition for a secondary battery electrode mixture layer according to claim 13 on a surface of a current collector.
16. A secondary battery, wherein: The secondary battery comprises the secondary battery electrode according to claim 15 .
Citation Information
Patent Citations
Binder for lithium cell, composition for producing electrode, and electrode
WO2014065407A1
Binder composition for non-aqueous secondary cell electrode, electrically conductive material paste composition for non-aqueous secondary cell electrode, slurry composition for non-aqueous secondary cell electrode, electrode for non-aqueous secondary cell, and non-aqueous secondary cell
WO2017150048A1
Electrode mixture for non-aqueous electrolyte secondary battery
WO2019054348A1
